PENGARUH INDEPENDENSI AUDITOR DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT (Studi Kasus Pada Kantor Akuntan Publik di Wilayah Bandung) - Nadya Dwi Wahyuni; Hiro Tugiman; Annisa Nurbaiti (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: The audit report produced by an auditor must be quality because audit report is share to the users of financial statement such as shareholders and investor as one basic for decision making. The users of financial statement expect the public accountant profession conduct independent and impartial assessment of the information presented by the company management in the financial statements. But in the practice there are many cases involving public accountant that impact on doubted the quality of audit. The population in this research is the all audiotrs who work at KAP in Bandung. The sample in this research is 54 auditors with using convenience sampling method. Data were analyzed using multiple regression linear. The result of this research provide empirical evidence that simultaneously variable of auditor’s independency and time budget pressure have a significant effect on audit quality. In partially variable of auditor’s independency and time budget pressure with positive direction have a significant effect on audit quality. Keywords: Auditor’s Independency, Time Budget Pressure, Audit Quality